PENGARUH IKLAN SUSU DAN PENGHASILAN KELUARGA TERHADAP PEMBERIAN ASI EKSKLUSIF - Enggar Enggar; Yuni Kristiani Tumani; Ni Made Rosiyana (Voice of Midwifery, 2022)
Breast milk is the best food for babies. Breastfeeding is carried out exclusively during the first 6 months of life, but in giving it, there are several factors that can influence it. The purpose of the study was to determine how the effect of milk advertising and family income on exclusive breastfeeding. This study used a cross sectional approach, the sample of this study were mothers who had babies aged 0-24 months. The sampling technique used purposive sampling with a total sample of 150 respondents. The results of the study of 150 respondents, seen from the milk advertising factor, 50.6% were interested in milk advertising (p = 0.020). Meanwhile, viewed from the income factor, 61.3% have income < UMK (p = 0.995). Conclusion: there is an effect of formula milk advertising on exclusive breastfeeding, but there is no effect of family income on exclusive breastfeeding.